2005
DOI: 10.1590/s1517-83822005000100015
|View full text |Cite
|
Sign up to set email alerts
|

Production of thermostable glucoamylase by newly isolated Aspergillus flavus A 1.1 and Thermomyces lanuginosus A 13.37

Abstract: Thirteen thermophilic fungal strains were isolated from agricultural soil, tubers and compost samples in tropical Brazil. Two strains were selected based on of their ability to produce considerable glucoamylase activity while growing in liquid medium at 45ºC with starch as the only carbon source. They were identified as Aspergillus flavus A1.1 and Thermomyces lanuginosus A 13.37 Tsiklinsky. The experiment to evaluate the effect of carbon source, temperature and initial pH of the medium on enzyme production was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 16 publications
5
43
0
Order By: Relevance
“…Fungal enzymes are more preferable to enzymes from other microorganisms because of their Generally Regarded as Safe (GRAS) status (Sindhu et al, 2009). Studies on fungal amylase especially in the developing countries have concentrated mainly on Aspergillus species probably because of ubiquitous nature and non-fastidious nutritional requirement of this organism (Abu et al, 2005;Gomes et al, 2005;Okolo et al, 2000).…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 307-325mentioning
confidence: 99%
“…Fungal enzymes are more preferable to enzymes from other microorganisms because of their Generally Regarded as Safe (GRAS) status (Sindhu et al, 2009). Studies on fungal amylase especially in the developing countries have concentrated mainly on Aspergillus species probably because of ubiquitous nature and non-fastidious nutritional requirement of this organism (Abu et al, 2005;Gomes et al, 2005;Okolo et al, 2000).…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 307-325mentioning
confidence: 99%
“…In the same study, the authors reported that the enzymes exhibited about 60% of residual activity after 1 h at 50°C. Gomes et al (2005) reported a decrease of approximately 30% in the catalytic activity of amylase produced by the fungus Thermomyces lanuginosus when incubated for 24 h at pH 4.0 and 10.0. However, the enzyme remained stable after 1 h at 60°C.…”
Section: Effect Of Ph and Temperaturementioning
confidence: 99%
“…A lot of focus is currently made on the high thermostability of glucoamylase used in the starch processing. Hence, a highly thermostable and environmentally compatible glucoamylase is very essential for industrial purposes [4]. The main benefits of using thermostable enzymes in the starch processing industry include increased reaction rates, decreased contamination risk and cost-reduction in terms of cooling system [5,6].…”
Section: Introductionmentioning
confidence: 99%